A virtual prototype for performance analysis of electropneumatic brake on metro trains. (June 2020) - Zuo, Jianyong; Ding, Jingxian; Liu, Cheng; Luo, Zhuojun
In order to facilitate system design and performance analysis, a virtual prototype for metro train electropneumatic brakes is proposed. A virtual braking environment that consists of a three-car train model and six electropneumatic brakes model is elaborated. The virtual braking environment can be used to research the relation between braking response and electropneumatic brake's parameters and to simulate axle loading transfer. By comparing the simulation results with bench test data, the electropneumatic brake model is proven to be quite accurate. Based on the proposed virtual prototype, a test train brake is designed, and a couple of field tests are carried out. The average deceleration of electropneumatic compound service brake at the initial speed of 45 km/h is 0.83 m/s 2, the braking distance is 94 m, and that of pure air service brake at the speed of 43 km/h is 0.64 m/s 2, the braking distance is 111 m. The field test results satisfy the test train requirements, which further proves the effectiveness of the proposed virtual prototype.